Mechanical damping in nanostructured Nd60Fe30Al10 magnetic alloys - Salva, Horacio Ramon (2010)
Nanostructured Nd60Fe30Al10 magnetic alloys were obtained by melt spinning at a tangential wheel speed of 5 m/s. Magnetic and stress relaxation processes were investigated in the as cast condition. Low frequency mechanical spectroscopy studies (dynamic elastic torsion modulus and internal damping  measurements) were conducted at fixed frequencies between 0.1 and 1 Hz, in the range [150 to 480 K].  The low temperature internal damping and dynamic elastic modulus exhibited a large heating cooling  hysteresis and two damping peaks: one due to a stress induced relaxation mechanism operating near  200K [1 Hz] and another one, at about 260 to 270 K, which could not be correlated with any step in the  modulus, indicating that it is not anelastic in origin. The high temperature damping was described by  an exponential background and a broad peak contribution centered at about 400K (1 Hz). The resulting  maximum is frequency dependent, but it is little sensitive to applied fields up to 30 mT. On contrary, the  elastic modulus behavior associated to this maximum resulted largely affected by frequency, the external  fields and the magnetic state of the sample.